WEFI Tool Package - McDougall, Cynthia; Kruijssen, Froukje; Sproule, Katie; Serfilippi, Elena; Rajaratnam, Surendran; Newton, Julie; Adam, Rahma (WorldFish, 2022)
The WEFI Tool Package includes the following files: A -WEFI: Abbreviated Womens empowerment in Fisheries Index; Pro-WEFI: Project Womens empowerment in Fisheries Index, WEFI DO files and pro-wefi questionnaire.